Short-Term Clinical Outcomes of Drug Eluting Stents in Diabetic versus Non-Diabetic Patients Having Stable Coronary Artery Disease - Adnan, Yasir; Noor, Lubna; Dar, Muhammad Habeel; Adnan, Haris; Hafizullah, Muhammad (International Journal of Pathology, 2018)
Background: Diabetes mellitus (DM) increases the risk of adverse outcomes after coronary arteryrevascularization. Diabetic patients have a worse prognosis than non-diabetic patients, with generally greaterrates of death, myocardial infarction and need for target lesion and vessel revascularization.Objectives: The aim of this study was to assess the Short-Term clinical outcomes in diabetic versus non-diabeticpatients who underwent successful percutaneous revascularization with drug-eluting stents.Material and Methods: Between April 2011 and July 2012, 144 diabetic and 232 non-diabetic patients withstable coronary disease undergoing DES implantation at Cardiology Unit Lady Reading Hospital, were enrolledprospectively. Clinical outcomes (Myocardial infarction [MI], unstable angina [UA], and positive ETT) at threemonths were measured in Diabetic and non-Diabetic patients who received DES for coronary artery lesions. Allpatients were followed and reassessed after 3 months from the index procedure. Exercise Tolerance Test (ETT)was performed on every patient and recorded on Proforma. Data analysis was done using SPSS version 16.Results: We evaluated 376 patients with stable coronary artery disease treated with DES of the 376 patients, 144(38.3%) were Diabetics. The mean age was57±9.313 years. Male patients were 271(72.1%). At 3-Months follow-up,diabetic patients treated with DES had significantly higher rates for myocardial infarction (5.6 vs. 1.3%; p = 0.025),unstable angina (12.5 vs. 3.4%; p = 0.001) and positive ETT (16.7 vs. 5.6%; p = 0.001).Conclusion: Our study revealed that despite the use of DES the risk of myocardial infarction, unstable angina,and positive ETT at three months remains higher in diabetic patients.